Effect of renal function and dialysis modality on daprodustat and predominant metabolite exposure - Caltabiano, Stephen; Cizman, Borut; Burns, Olivia; Mahar, Kelly M; Johnson, Brendan M; Ramanjineyulu, Bandi; Serbest, Gulyeter; Cobitz, Alexander R (Clinical kidney journal, 2019)
Abstract Background Current therapies for anemia of chronic kidney disease (CKD) include administration of supplemental iron (intravenous and/or oral), blood transfusions and replacement of erythropoietin through the administration of recombinant human erythropoietin (rhEPO) and rhEPO analogs, each with limitations. Daprodustat is an orally active, small molecule hypoxia-inducible factor-prolyl hydroxylase inhibitor that is currently in Phase 3 clinical studies. As it is well appreciated that the kidney represents a major route of elimination of many drugs, and daprodustat will be administered to patients with advanced CKD as well as patients with end-stage kidney disease, it is important to characterize the pharmacokinetic profile in these patient populations to safely dose this potential new medicine. Methods The primary objective of these studies, conducted under two separate protocols and with identical assessments and procedures, was to characterize the steady-state pharmacokinetics of daprodustat and the six predominant metabolites (i.e. metabolites present in the highest concentration in circulation) in subjects with normal renal function, anemic non-dialysis (ND)-dependent CKD subjects (CKD Stage 3/4) and anemic subjects on either hemodialysis (HD) or peritoneal dialysis (PD). All enrolled subjects were administered daprodustat 5 mg once daily for 14 days (all except HD subjects) or 15 days (for HD subjects). Blood, urine and peritoneal dialysate were collected at various times for measurement of daprodustat, predominant metabolite, erythropoietin and hepcidin levels. Results The pharmacokinetic properties of steady-state daprodustat peak plasma concentration (Cmax), area under the plasma daprodustat concentration-time curve (AUC) and the time of Cmax (tmax) were comparable between all cohorts in this study. In addition, there was no clinically relevant difference in these properties in the HD subjects between a dialysis and ND day. For CKD Stage 3/4, HD (dialysis day) and PD subjects, the AUC of all daprodustat metabolites assessed was higher, while the Cmax was slightly higher than that in subjects with normal renal function. Over the course of the 14 or 15 days of daprodustat administration, hemoglobin levels were seen to be relatively stable in the subjects with normal renal function, CKD Stage 3/4 and PD subjects, while HD subjects had a decrease of 1.9 gm/dL. All renally impaired subjects appeared to have similar erythropoietin responses to daprodustat, with approximately a 3-fold increase in these levels. In subjects with minimal to no change in hemoglobin levels, hepcidin levels remained relatively stable. Daprodustat, administered 5 mg once daily for 14–15 days, was generally well tolerated with a safety profile consistent with this patient population. Conclusion These studies demonstrated no clinically meaningful change in the pharmacokinetic properties of daprodustat when administered to subjects with various degrees of renal impairment, while for CKD Stage 3/4, HD (dialysis day) and PD subjects, the Cmax and AUC of all daprodustat metabolites assessed were higher than in subjects with normal renal function. Administration of daprodustat in this study appeared to be generally safe and well tolerated.